Anemia in Indian men predicts fewer work hours and lower earnings: Evidence from nationally representative health and labor surveys - Scott, Samuel P.; Pant, Anjali; Nguyen, Phuong Hong; Alderman, Harold; Yadav, Kapil; Menon, Purnima (American Society for Nutrition, 2020)
Anemia is globally recognized as an important public health problem in women and children, thus the consequences of anemia have predominantly been described in these two groups. India's large population, high anemia prevalence and male-dominated workforce imply that productivity consequences of anemia in men could have large implications. We sought to explore the association between local anemia rates and productivity outcomes in Indian men.